Diplomatic service (Nature (London), 2014)
Almost 60 years after the launch of the first Soviet satellite Sputnik startled US President Dwight Eisenhower into appointing James Killian as his nation's first scientific adviser, Killian's modern equivalents from around the world will meet in New Zealand this week for their own conference. They will, presumably, keep their mobile phones switched on.